Anxiety contribution on students’ text comprehension in various test types - Supeno Supeno; Imam Suseno (Journal of Education and Learning (EduLearn), 2020)
This study aims to understand how anxiety as a variable contributes to affect the ability in comprehending English texts evaluated on students’ performance on various test types, namely 1) multiple-choice tests (MC), 2) fill-in-the-blank tests (FTB), and 3) true/false tests (TF). This research used ex post facto method, with responses collected from eleventh grade high school students in Jakarta. Respondents worked on tests with similar material, although at different times. Students’ anxiety was measured based on behavioral and cognitive characteristics listed on the questionnaire given to respondents along with the English test. The results pointed out that there was indeed a difference ofstudents’ anxiety levels in working on the various English text comprehension tests given. The results of the English text comprehension tests were generally influenced by the anxiety variable, although the effect was found to be small. Teachers are recommended to apply multiple variations of ability evaluation in measuring the students’ English text comprehension by using multiple test modes.